Afro-Autarky. Onjangos and Utopias of Contemporary Angolan Activism - Blanes, Ruy Llera; Samussuku, Hitler (Critical Times, 2022)
This dispatch examines contemporary activist movements in Angola and their political utopias, namely their relevance to citizenship and governance, and their increasing importance in the political landscape. The authors describe the civic mobilization toward the implementation of a municipal electoral system (autarquia) and argue that it poses an Afro-utopian challenge: the issue of autarky, or the recognition of self-organization and self-sufficiency vis-à-vis postcolonial autocratic rule.